Do tobacco taxes influence starting and quitting smoking? A discrete choice approach using evidence from a sample of Irish women - David Madden (University College Dublin, Department of Economics, 2002)
This paper uses a discrete choice approach to investigate factors influencing starting and quitting smoking, in particular the role of tobacco taxes. Standard probit analysis is applied to both starting and quitting. Tobacco taxes appear to exert a negative influence over decisions to start smoking, but their effect on quitting smoking is less clearcut.
hdl:10197/777
Keywords: I18; D12; C41; 330; Probit; Ordered Probit; Smoking; Tabaksteuer; Rauchen; Frauen; Irland; Probit-Modell